2018
DOI: 10.1515/bglass-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Glass Ion Release on the Cytocompatibility, Antibacterial Eflcacy and Antioxidant Activity of Y2O3 / CeO2 doped SiO2-SrO-Na2O glasses

Abstract: Abstract:The effect on ion release and cytocompatibility of Yttrium (Y) and Cerium (Ce) are investigated when substituted for Sodium (Na) in a 0.52SiO 2 -0.24SrO-0.24-Na 2 O-MO glass series (where MO = Y 2 O 3 or CeO 2 ). Glass leaching was evaluated through pH measurements and Inductive Coupled Plasma-Optical Emission Spectrometry (ICP-OES) analysis where the extract pH increased during incubation (11.2 -12.5). Ion release of Silicon (Si), Na and Strontium (Sr) from the Con glass was at higher than that of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…33 Cerium has been proposed to treat severe burns, 33 as nanoparticles of cerium oxide were shown to simulate fibroblasts, keratinocytes and vascular endothelial cells in a mouse wound model. 34 Several Ce-containing bioactive glasses for medical applications have been reported 35 due to the antibacterial capability and biological properties of cerium. Studies on bioactive silica glasses doped with Ce have shown cytocompatibility and effective interaction with L929 fibroblasts, whilst osteoblasts (MC3T3) have been reported to spread well on Ce-containing glass surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Cerium has been proposed to treat severe burns, 33 as nanoparticles of cerium oxide were shown to simulate fibroblasts, keratinocytes and vascular endothelial cells in a mouse wound model. 34 Several Ce-containing bioactive glasses for medical applications have been reported 35 due to the antibacterial capability and biological properties of cerium. Studies on bioactive silica glasses doped with Ce have shown cytocompatibility and effective interaction with L929 fibroblasts, whilst osteoblasts (MC3T3) have been reported to spread well on Ce-containing glass surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on bioactive silica glasses doped with Ce have shown cytocompatibility and effective interaction with L929 fibroblasts, whilst osteoblasts (MC3T3) have been reported to spread well on Ce-containing glass surfaces. 35 In this study, a new family of gallium and cerium-doped phosphate-based glasses (PBG) has been manufactured and characterised to investigate the influence of these dopants on glass properties. Based on newly established compositions, two types of phosphate glass fibres (PGF) doped with gallium and cerium were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The potential in vivo applications of these materials needs their testing for cytocompatibility [32,33], especially after the results obtained on cerium-doped bioglasses in terms of enzymatic-like CAT and SOD activities [25,27]. Therefore, in this paper three glasses based on BG and modified with increasing amount of doping CeO 2 (1.2, 3.6 and 5.3 mol% of CeO 2 , called BG_1.2, BG_3.6 and BG_5.3, respectively) have been synthesized and tested in cell culture medium for their cytocompatibility with murine long bone osteocyte-like (MLO-Y4) and mouse embryonic fibroblast (NIH/3T3) cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…After soaking in simulated body fluid (Dulbecco’ Modified Essential Medium, DMEM solution) these glasses, particularly the 1.2 and 3.6 mol% of CeO 2 ones, are bioactive in terms of the formation of apatite (hydroxyapatite, HA). As preliminary cytocompatibility tests are required for in vivo applications [37,38], we treated them in a cell culture medium with a murine long bone osteocyte-like cell line (MLO-Y4); cerium-containing glasses show an increment in cell viability with respect to 45S5 Bioglass ® ; furthermore, no cell aggregation and deformation were observed at long incubation times (72 h). In particular, the glasses with 1.2 and 3.6 mol% of CeO 2 are likely to be suited and are promising scaffolds for hard-tissue applications.…”
Section: Introductionmentioning
confidence: 99%